Knowledge and practices regarding the handling of neonatal incubators among nursing professionals - Costa, Claudia Carolina [UNESP]; Pamplona Tonete, Vera Lucia [UNESP]; Garcia de Lima Parada, Cristina Maria [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2017)
Objectives: To compare knowledge and practices regarding the handling of neonatal incubators among nurses and nursing technicians/aides. Methods: This was a cross-sectional study conducted at the neonatal unit of a reference hospital, with data obtained via a questionnaire about the professionals' knowledge and direct, structured and nonparticipant observation of nursing team practices when handling incubators. The researchers developed a score to represent the adequateness of the practices observed. Results: No difference was observed between the two studied groups in terms of knowledge in handling incubators, except for knowledge about the benefit of humidification, cited mostly by nurses (p=0.040). No differences were observed when comparing practice scores obtained individually and the overall score (p=0.723). The incubator practices of nursing technicians/aides and nurses were 70% adequate, which is a low percentage considering the hospital's high complexity. Conclusion: In general, there was no difference between the nursing team members with regards to the studied knowledge and practices.
Keywords: Incubators, infant; Infant, newborn; Biomedical technology; Nursing, team; Neonatal nursing